New considerations on the acropolis of Butrint during the Archaic age - Federica Carbotti (Groma, 2023)
The paper discusses the current state of research in relation to the archaic phases of Butrint (Southern Albania), one of the few sites of ancient Epirus with important archaeological evidence dating back to the Archaic period. The international archaeological missions that have investigated the acropolis of the site over the last century have brought to light few but clear traces of frequentation of the area. Pottery, an ash altar and roof tiles suggest that this was probably a cult place: the proximity and control of Corcyra over the mainland makes it plausible that the island had a role in shaping its appearance, however its features are still debated. The recent excavations and topographical surveys of the University of Bologna offer the opportunity for a new analysis of the historical and archaeological context in which Archaic Butrint is framed, as well as, at the same time, put forward open research questions that will need to be developed by future excavation campaigns.